Актуальность акмеологическго подхода к формированию конкурентоспособности будущего специалиста-психолога в условиях высшего учебного заведения - Сокольская, Н. А. (НТУ "ХПІ", 2009)
В современных условиях наблюдается высокая конкуренция среди высших учебных заведений при подготовке будущих специалистов-психологов. Поэтому при решении задач повышения уровня профессиональной подготовки особое внимание должно уделяться интеллектуальному, нравственному, культурному развитию, профессиональному росту и творческой самостоятельности будущего специалиста.

There is topically in our days a high competition among higher educational establishments at preparation of future specialists-psychologists. There for the special attention must be spared intellectual, moral, cultural development, professional growth and creative independence of future specialist at the decision of tasks of increase of level of professional preparation.
Actuality of akmeologicheskgo approach to forming of competitiveness of future specialist-psychologist in the conditions of higher educational establishment
Keywords: образование высшее; подготовка профессиональная; компетенция